The intention to use social media in higher learning institution / Rozana Othman and Nurul Ezaili Alias - Othman, Rozana; Alias, Nurul Ezaili (Universiti Teknologi MARA, Cawangan Melaka, 2017)
The rapid evolution of technology and internet application has led to the expansion of social media. This social media are labelled as vital channel to connect and transmitted the knowledge between people and this tools has been utilized by educators and learners. This study investigated the factors that affecting student’s intention to use social media for learning by using the social media acceptance model (SMAM) in a higher learning institution. By using convenience sampling technique, a total of 101 students has responded valid questionnaires via online survey and it gives an average response rate of 89% for the study. Data gathered were initially analyzed using SPSS version 22.0. The findings of Multiple Regression Analysis revealed the significant relationship between Self and Performance on students’ intentions to use social media. However Effort and Communication Functionality has no significant relationship on students’ intentions to use social media. Additionally, the analysis revealed that the most influence factor that affects toward students’ intentions to use social media was Self.